Lanthanum‐Induced Gastrointestinal Histiocytosis. Issue 3 (April 2015) - Rothenberg, Michael E.; Araya, Hiwot; Longacre, Teri A.; Pasricha, Pankaj J.
Abstract : N/A: A patient with end‐stage renal disease (ESRD) on hemodialysis presented with fever, anorexia, and nausea shortly after starting oral lanthanum carbonate for phosphate control. Gastric and duodenal biopsies demonstrated diffuse histiocytosis with intracellular aggregates of basophilic foreign material. Transmission electron microscopy, an underutilized diagnostic test, revealed the nature of the aggregates as heavy metal particles, consistent with lanthanum. Symptoms and histiocytosis improved after discontinuation of lanthanum. Lanthanum may be an underdiagnosed cause of gastrointestinal histiocytosis.